Demosthenes, De Corona §§ 169-170 in P.CtYBR inv. 4671 - Kreij, Mark de (De Gruyter, 2018)
Abstract: A scrap of papyrus from the Beinecke library, dating to the late first century BCE or early first century CE, has yielded a passage from Demosthenes’ De Corona. The text is good, and in one place offers further support for Demosthenes’ avoidance of hiatus.
Aus: Archiv für Papyrusforschung und verwandte Gebiete, 61 (23 September 2015), Nr. 1. pp. 32-36. ISSN 1867-1551
Keywords: Demosthenes -- v384-v322